Energy and exergy analysis of spark ignited engine fueled with Gasoline-Ethanol-Butanol blends - Ibrahim Thamer Nazzal; Mohammed kamil (AIMS Energy, 2020)
This study focused on energy and exergy analysis of spark ignition engine that is fueled with gasoline-ethanol, gasoline-butanol, and gasoline-butanol-ethanol blends. The analysis was performed based on the experimental data at different engine speeds. With these data, a comparison for the energy and exergy analysis between used fuel blends were performed. It was found that, compared with ethanol-gasoline, butanol-gasoline has the highest brake power, exergy losses through a heat transfer and exhaust gases, brake thermal and exergertic efficiency. In contrast, exergy destruction has presented low values when the engine fueled with butanol-gasoline and the highest values when was fueled with ethanol-gasoline. Moreover, the moderate value of the brake power, exergy losses through a heat transfer and exhaust gases, exergy destruction, brake thermal, and exergertic efficiency was presented by ethanol-butanol-gasoline blend. The finding results of the exergy analysis have indicated that butanol-gasoline can offer a competitive alternative instead of ethanol-gasoline fuel in spark-ignition engines since it is the closest to the gasoline in terms of the energy and exergy distribution.